Methods for Connecting a Concentrically Shaped Sensing Element of Microaccelerometers on Surface Acoustic Waves - M. A. Sorvina; A. S. Kukaev (Известия высших учебных заведений России: Радиоэлектроника, 2024)
Introduction. At present, acceleration sensors are in demand in various areas, from consumer electronics to space technology. Microaccelerometers exhibit the advantages of compact dimensions, light weight, and ease of integration with other components. The most common accelerometers are based on microelectromechanical systems. However, due to the fragility of elastic suspensions, these devices are characterized by low impact resistance, which impedes their application in highly dynamic objects with accelerations of up to 50 000 g. The authors propose to use microaccelerometers based on surface acoustic waves, which are solid-state monolithic structures capable of withstanding high shock loads. Previous work has proposed the concept of concentric electrodes, which are more energy efficient compared to linear designs. However, concentric elements are difficult to connect to the electrical circuit, due to the impossibility of connecting the busbars directly. Therefore, the authors describe and simulate five alternative methods for connecting the sensing element of such devices.Aim. To select an optimal method for connecting the sensing element of microaccelerometers from the standpoint of maintaining the integrity of the electrodes and ensuring minimal influence on the propagation of surface acoustic waves.Materials and methods. Finite element simulation in the COMSOL Multiphysics software.Results. Five connection methods, including point-to-point wiring, removing the electrode sector, filling holes in the electrodes and substrate with metal, pulling wires through holes in the substrate and bringing out contact bars along the side face, were proposed and analyzed. Computer simulation was carried out. Graphs of the amplitude-frequency characteristic are presented.Conclusion. Among the considered methods for connecting the sensing element, the most appropriate seems to be method No. 3, which implies holes in the electrodes and contacts on the bottom side of the substrate. Here, the graph of the amplitude-frequency characteristic practically coincides with that of the sensor without connections (reference). Future work will focus on creating a prototype and its experimental testing.